2022
DOI: 10.1021/acsanm.2c00107
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Microwave Synthesis of Co3O4/In2O3 Nanostructures for Photoelectrocatalytic Reduction of Cr(VI)

Abstract: Co3O4/In2O3 nanocomposites were prepared via a microwave-hydrothermal method and directly used as photoanodes for the photoelectrocatalytic (PEC) process to reduce Cr­(VI). The as-prepared Co3O4/In2O3 composites show a rod-like structure, which is composed of nanoparticles. The PEC experiments indicated that after 120 min of irradiation with 0.7 V bias voltage and visible light, the Cr­(VI) reduction efficiency of Co3O4/In2O3 composites in aqueous solution was 100%, which was superior to the samples prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 67 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…The study found that photocatalytic technology has more advantages than other traditional physical, chemical, or biological technologies in removing organic dyes or pathogenic bacteria. , Photocatalytic technology has the advantages of mild reaction conditions, low energy consumption, high efficiency, and no secondary pollutants. It has achieved fruitful results in many fields such as organic pollutant degradation, , water splitting, heavy metal reduction, polluted water treatment, and antibacterial, showing great application prospects. For example, a typical g-C 3 N 4 /TiO 2 nanocomposite has been reported to have a removal rate of 91.2% for fluoride ions within 30 min under visible light .…”
Section: Introductionmentioning
confidence: 99%
“…The study found that photocatalytic technology has more advantages than other traditional physical, chemical, or biological technologies in removing organic dyes or pathogenic bacteria. , Photocatalytic technology has the advantages of mild reaction conditions, low energy consumption, high efficiency, and no secondary pollutants. It has achieved fruitful results in many fields such as organic pollutant degradation, , water splitting, heavy metal reduction, polluted water treatment, and antibacterial, showing great application prospects. For example, a typical g-C 3 N 4 /TiO 2 nanocomposite has been reported to have a removal rate of 91.2% for fluoride ions within 30 min under visible light .…”
Section: Introductionmentioning
confidence: 99%
“…4 As such, a foremost research theme in materials science is the advancement of novel methodologies for environmental remediation 5 and it has resulted in several new processes, such as membrane filtration, photochemical degradation, reverse osmosis, ozonation, ion exchange, biodegradation, precipitation/oxidation, electrocoagulation, and adsorption, and are commonly used in dye removal processes to protect water quality. 6–10 Dye removal via adsorption is the preferred method as no hazardous components are produced. 11–13…”
Section: Introductionmentioning
confidence: 99%
“…4 As such, a foremost research theme in materials science is the advancement of novel methodologies for environmental remediation 5 and it has resulted in several new processes, such as membrane filtration, photochemical degradation, reverse osmosis, ozonation, ion exchange, biodegradation, precipitation/oxidation, electrocoagulation, and adsorption, and are commonly used in dye removal processes to protect water quality. [6][7][8][9][10] Dye removal via adsorption is the preferred method as no hazardous components are produced. [11][12][13] In the past few decades, [14][15][16][17][18] supramolecular gels based on low molecular weight organogelators (LMOGs) have gained significant attention due to an extensive range of potential applications, such as drug delivery, 19 template reactions, 20 materials and devices fabrication, 21 molecular sensing, 22 and oil-spill recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports on photocatalytic Cr(VI) reduction suggest that the electrons in the conduction band, generated after photoexcitation of the catalytic materials, are mainly responsible for photoreduction. 45,46 Therefore, in the present study, an experiment was conducted with AgNO 3 as an electron-trapping agent to shed more light on the mechanism of the photocatalytic reaction using hybrid 1 as a model catalyst. It was found that the presence of AgNO 3 in the reaction medium results in quenching the photocatalytic activity of hybrid 1.…”
Section: ■ Introductionmentioning
confidence: 99%